Dural sinos thrombosis in patients with mastoiditis - Ferreira, Fernanda; Marnoto, Dina; Ribeiro, António; Carreiro, Inês; Moura, Cristina; Frade, Maria João; Sousa Fernandes, J. (Portuguese Journal Internal Medicine, 1999)
Cerebral venoocclusive disease is recognized as a uncommon clinical entity with a high mortality rate. lt may involve the major venous sinus, superficial cortical veins or deep venous system. The clinical diagnosis can be difficult and therefore the appropriate therapy due to the non-specific clinical settings. We report, making a review of the literature, two clinical cases with unsuspected durai sinus thrombosis and distinct clinicai settings in whom sinus trombosis and mastoiditis was found.